Trend in the developments of the electric vehicles (EV) and policy towards its implementation - Ong, Tin Fong. (2012)
Implementation of Electric Vehicles (EVs) has been widely recognised as a potential solution to reduce the dependency on fossil fuel and limiting the amount of emissions attributed to the transport sector. Governments view this as part of sustainable transport to pave the way for economical growth and to build a competitive edge for advanced energy technologies while car makers see EVs as having a bright future in the transport sector. Moving ahead, it is necessary to keep abreast on the technological developments in the EVs market as well as policy initiatives of the various governments to propose suitable plans for the future developments of Singapore’s transport sector.It is found that almost 90% of the population had heard about EVs and more than 70% are willing to adopt the use of EV in future. Implementation of EV can be a success if preferences of Singaporeans are met and most importantly, the price is not too steep.